Development of high-temperature oxide melt solution calorimetry for p-block element containing materials. Issue 16 (28th August 2020) - Abramchuk, Mykola; Lilova, Kristina; Subramani, Tamilarasan; Yoo, Ray; Navrotsky, Alexandra
Abstract: Abstract : Understanding the thermodynamic stability of materials plays an essential role in their applications. The high-temperature oxide melt solution calorimetry is a reliable method developed to experimentally measure formation enthalpy. Until now, it has been mostly used for the characterization of oxide materials. We introduce modifications in the experimental technique which makes it suitable for a wide range of non-oxide compounds. The modified methodology was used to measure the heat effects associated with the oxidative dissolution of almost all p -elements of groups III, IV, V, and VI and verified by calculating the standard enthalpies of formation of the corresponding oxides at 298 K. The results presented serve as a compelling database for pure p -elements, which will provide a very straightforward way of calculating the formation enthalpies of non-oxide systems based on high-temperature calorimetric experiments.